Enterocolic Lymphocytic Phlebitis Treated Preoperatively with Biologics and Immunosuppressive Agents - Soh Okano; Takashi Yao; Osamu Nomura; Akihito Nagahara; Toshiaki Hagiwara; Kiichi Sugimoto; Makoto Takahashi; Kazuhiro Sakamoto (Case Reports in Pathology)
Enterocolic lymphocytic phlebitis is phlebitis of unknown etiology in which lymphocytes affect veins without arteries and shows evidence of systemic vasculitis in the intestinal wall and mesentery, mainly in the small intestine and colon. Although patients present with a variety of gastrointestinal symptoms and findings like those of inflammatory bowel disease or ischemic bowel disease, there are no specific findings for enterocolic lymphocytic phlebitis. As a result, a diagnosis tends to be made after surgery. There are few case reports of enterocolic lymphocytic phlebitis, and the impact of chronic courses and immunosuppressive drugs on enterocolic lymphocytic phlebitis is not well known. A 47-year-old man was treated with infliximab and steroids for unexplained ulceration and narrowing of the ileocecal area, which was suspected to be inflammatory bowel disease with atypical findings. Lymphocytic phlebitis was noted in the surgical specimen, and enterocolic lymphocytic phlebitis was diagnosed. No recurrence of enterocolic lymphocytic phlebitis was observed postoperatively. This disease should also be considered among patients with inflammatory bowel disease-like lesions that do not respond to infliximab or steroids.